Concentrations and mass fluxes estimation of organochlorine pesticides in Three Gorges Reservoir with virtual organisms using in situ PRC-based sampling rate. (February 2016) - Temoka, Cedrique; Wang, Jingxian; Bi, Yonghong; Deyerling, Dominik; Pfister, Gerd; Henkelmann, Bernhard; Schramm, Karl-Werner
Abstract: Organochlorine pesticides (OCP) are widely distributed environmental pollutants. Due to their persistence and toxicity, it is important to know their fluxes and spatial and temporal distribution in the environment. In this study, a new procedure to estimate OCP concentration based on a set of performance reference compounds (PRCs) was used. Their occurrence and mass fluxes were assessed on a regional scale ranging from Chonqging to Maoping in Three Gorges Reservoir (TGR) as part of Yangtze River. The results are based on three sampling campaigns in 2009 (twice) and 2011. Due to different factors, the measured concentrations varied from 410 to 1418 pg/L. The highest total OCP concentration was localized in Wanzhou while the lowest was downstream Maoping near the Three Gorges Dam (TGD). The highest load of OCP mass fluxes was observed at Wanhzou with 9.6 mg/s and the lowest load at Maoping with 2.97 mg/s. Studies at Maoping show an increase in OCP water concentration from 2009 to 2012. Comparison between free dissolved OCP water concentration and total OCP water concentration in TGR 2009, 2011 and 2012 show a slight variation, indicating the important role of dilution in the OCP removal process in TGR. Highlights: New procedure based on 16 13C-labeled PAH-PRC field data and uncertainty is developed to estimate OCP sampling rate The dominating OCP in TGR in 2009 and 2011 were α-, β-, γ-HCH, HCH, PeCB, PeCA, dichlorodipenyl and Endosulfan OCP concentration decreases in CQ following the decline of the agricultural sector in this area Mass balance of OCP in TGR shows a dissipation by a factor of 2-3 based relative to their impact Wanzhou seems a potential source of OCP in TGR